RETINOPATHY OF PREMATURITY IN TERTIARY REFERRAL EYE HOSPITAL IN INDONESIA: CHARACTERISTICS AND MANAGEMENT: Oral Presentation - Observational Study - Resident - RAISHA PRATIWI INDRAWATI; Mayasari Wahyu Kuntorini; Sesy Caesarya; Primawita O. Amiruddin; Irawati Irfani; Feti Karfiati Memed (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Retinopathy of prematurity (ROP) is a vasoproliferative disorder of the retina that occurs in premature infants. Incidence of ROP is higher in middle- and lower-income countries, including Indonesia; hence information about the characteristics of the patients is essential to make strategies regarding its management. The aim of this study is to describe the characteristics and managementof patients with retinopathy of prematurity at the National Eye Center, Cicendo Eye Hospital. Methods : Data were obtained retrospectively from medical records from January 2018 until December 2020 using ICD-10 coding for retinopathy of prematurity. Variables include demographic data, clinical characteristics, and management. Results : In total, 177 patients (340 eyes) were included in this study. Demographically, 53.7% of the patients were boys; 67.8% came from West Java; 93.2% were referred; and 85.9% were health coverage users. The mean gestational age was 29.9±2.6 weeks and the mean birth weight was 1415.6±393.1 grams. Most of the patients have bilateral conditions and already have stage 5 ROP, regardless of their gestational age and birth weight. Conservative management was given to 95.5% of stage 5 ROP patients. As many as 50% of stage 4 patients underwent pars plana vitrectomy, and 85.4% stage 3 patients were managed by laser photocoagulation. Those in earlier stages were mainly observed first. Conclusion : Patients with ROP at Cicendo Eye Hospital mostly came in the advanced stage of the disease with conservative management. Early screening, timely referral, and prompt treatment are recommended in order to prevent blindness in premature infants.